Modeling and experimental validation of nanophotonics-enhanced solar membrane distillation technology for treating reverse osmosis brine - Mayar Elrakhawi; Ahmed F. Tayel; Amr Abdelrazek; Ze He; Qilin Li; Ibrahim A. Said (Applied Water Science)
Abstract A novel, cost-efficient Nanophotonic Enhanced Solar Membrane Distillation (NESMD) system, a solar-driven water desalination technology, was studied. The system features a photothermal membrane acting as a solar collector for water distillation, thus eliminating the need for an external condenser. To address the system’s vulnerability to thermal losses, a comprehensive mathematical model was developed and validated against real-world experimental data. This model represents intricately coupled heat and mass transfer within a sweeping-air NESMD system, incorporating heat loss considerations. The modeling strategy involved dividing the NESMD module into sub-cells and implementing a finite difference method for detailed analysis. This led to a series of nonlinear simultaneous equations, which were resolved via computational code using MATLAB software. The developed NESMD model exhibited commendable conformity to experimental data, exhibiting a relative percentage error of less than 10% for average permeate flux and identifying thermal losses as high as 63%. Depending on the operating conditions, heat transferred to the surroundings takes the lead among the heat loss contributors at higher feed rates (up to 25%), whereas heat conduction across the membrane dominates (up to 42%) thermal losses at low feed rates. The study established an exponential correlation between permeate production and solar energy, with a heat transfer coefficient ranging from 9.5 to 30 W m−2 K−1 and a coefficient of determination of 0.96. An integral part of this work includes calculating solar energy utilization and clarifying the system’s performance. Furthermore, this study examines the influence of diverse operational and geometric parameters, providing insights into enhancing production rates. Hence, an increase in feed layer thickness enhances freshwater production by 7%. Due to the intensification of solar irradiance, freshwater production increased ninefold, and specific energy consumption decreased by 134 kW hr m−3. This research underscores the potential of NESMD for sustainable desalination, providing a validated model that lays the groundwork for future advancements in membrane distillation technology.